PENGARUH KEADAAN DIRI,UNSUR PENYOKONG DAN FAKTOR DEMOGRAFI TERHADAP TEKAD KEWIRAUSAHAAN MAHASISWA PERGURUAN TINGGI DI PROVINSI RIAU: The Effect of Self-Condition, Supply Elements and Demographic Factors on the Entrepreneurship of Higher Education Students in Riau Province - Sukarni Sukarni; Norasmah Othman (UIR Press, 2019)
This study identifies factors that influence the determination of entrepreneurial. Thereare five for influence elements of determination entrepreneurial: self-efficacy,achievement motivation, facilitates capital, social relationships and entrepreneurialknowledge. A questionnaire was distributed to 389 university students. Finding shownthat the majority of students agreed that entrepreneurial knowledge, self-efficacy,achievement motivation and facilitates capital of key factors do influencedentrepreneurial determination. AMOS path analysis was used to identify thecontribution of the direct and indirect influence of the five dimensions ofentrepreneurial determination. Several hypotheses have been tested and found thatentrepreneurial determination influenced by entrepreneurial knowledge, self-efficacy,achievement motivation and facilitates capital. However, gender, financial supportand group activities did not moderate the entrepreneurial determination, whereasstudent residence do moderate to entrepreneurship determination. Furthermore, selfefficacydo moderated by gender, student residence and group activities, but financialsupport do not moderate self-efficacy. Gender, student residence, financial supportand group activities did not moderate achievement motivation. Finally the studyproposes guidelines to develop an effective entrepreneurship curriculum for universityin the Riau Province.Key words: entrepreneurial determination, self-efficacy, achievement motivation,facilitates capital, social relationships, student residence, entrepreneurialknowledge